Removal of Lead and Chromium From Industrial Wastewater by LocallyCitrobacter spp.Isolates - K. H. Aloosh, Maiada; N. A. Al- Azzawi, Mohammad. (Iraqi Journal of Science, 2023)
Biosorption is an effective method to remove toxic metals from wastewaters. In thisstudy biosorption of lead and chromium ions from solution was studied usingCitrobacter freundii and Citrobacter kosari isolated from industrial wastewater. Theexperimental results showed that optimum grwoth temperature for both bacteria is 30oCand the optimum pH is 7 &6 for C. freundii and C. kosari respectively. While theoptimum incubation period to remove Pb and Cr for C. freundii and C. kosari is 4 daysand 3days respectively. Also the biosorption of Pb and Cr in mixed culture of bacteriaand mixed culture of Pb and Cr was investigated. Result indicate that uptake of Cr andPb for C.freundii, C. kosari and in mixes culture of both bacteria is 58%, 53% and 82%respectively for chromium in solution containing 1000ppm of Cr and 59%, 63% and78% respectively for lead in solution containing 1000ppm of lead. But the uptakedecreases in solution containing both heavy metals lead and chromium.